Investigation of Alkaline Leaching Parameters on Stibnite Concentrate - ÇETİNER, BURCU NİLGÜN; AKTAŞ, SERDAR (SPRINGER HEIDELBERG, 2020)
According to critical statistical studies, antimony is one of the rarest elements in the world, and global resources could be exhausted by 2050. In light of these observations, its extraction will be costly due to poor-quality ore, deep mining, remote locations, and high energy consumption. In the present study, an alkaline leaching process was carried out on stibnite concentrate to evaluate the effect of reaction parameters on the percentage of antimony extraction. The leaching efficiencies of different sulfur and hydroxide sources were studied and compared to one another to create a better understanding of the reaction process. Kinetic models were investigated to identify the reaction pathway and calculate the activation energy. The activation energy of the stibnite dissolution was assessed as 19.13 kJ/mol using a two-dimensional diffusion-reaction model. The value of activation energy indicates the quantity of energy necessary for a reaction to proceed. As expected, potassium hydroxide leaching was significantly more successful than was sodium hydroxide; however, in terms of economics, the use of sodium hydroxide was found to be more cost-efficient. Interestingly, this finding indicated that caustic leaching is still the most effective method for stibnite extraction.
Keywords: Stibnite; Antimony; Alkaline; Leaching; Extraction; GOLD ORE; ANTIMONY; KINETICS; CYANIDATION; EXTRACTION; ACID